Validity of the multiple‐stimulus without replacement preference assessment for edible items. Issue 3 (19th April 2020) - Fritz, Jennifer N.; Roath, Christopher T.; Shoemaker, Patricia T.; Edwards, A. Blair; Hussein, Louisa A.; Villante, Natalie K.; Langlinais, Channing A.; Rettig, Lisa A.
Abstract : Studies have shown that the multiple‐stimulus without replacement (MSWO) preference assessment is an effective assessment format for identifying preferred items. However, it is possible that factors other than reinforcer quality might influence selections by some individuals when the MSWO array consists of edible items. The validity of the MSWO results was evaluated by comparing items identified as most and least preferred by the MSWO assessment in a concurrent‐schedule (CS) format. Varying edible items were used in each study. The MSWO format accurately identified the higher quality edible item for most participants across studies (76%); however, the MSWO format did not predict the highest quality edible item in the CS assessment for 20% to 30% of participants in each study.